Mapping the distribution of conformational information throughout a protein sequence - Gebhard, Leopoldo German (2006)
The three-dimensional structure of protein is encoded in the sequence, but many amino acid residues carry no essential conformational information, and the identity of those that are structure-determining is elusive. By circular permutation and terminal deletion, we produced and purified 25 Bacillus licheniformis β-lactamase (ESBL) variants that lack 5–21 contiguous residues each, and collectively have 82% of the sequence and 92% of the non-local atom–atom contacts eliminated. Circular dichroism and size-exclusion chromatography showed that most of the variants form conformationally heterogeneous mixtures, but by measuring catalytic constants, we found that all populate, to a greater or lesser extent, conformations with the essential features of the native fold. This suggests that no segment of the ESBL sequence is essential to the structure as a whole, which is congruent with the notion that local information and modular organization can impart most of the tertiary fold specificity and cooperativity.